A Stopped-Flow Apparatus with Light-Scattering Detection and Its Application to Biochemical Reactions - Riesner, Detlev (1973)
A stopped-flow apparatus utilizing light-scattering for following the progress of a reaction is described. The method is applicable to all reactions that result in a significant change of the average molecular weight. It was possible due to several modifications of a conventional stopped-flow system to obtain a sensitivity comparable to that of commercial instruments for static light-scattering measurements. Experiments on three reactions are reported: association and dissociation of mercury ligands with DNA, dissociation of the dimers of DNA-dependent RNA polymerase, and complex formation of tRNA(Ser) (yeast) with the cognate aminoacyl-tRNA synthetase. The changes in the intensities of the scattered light are calculated and compared with the measured amplitudes.